Pengelolaan Sistem Informasi Manajemen Pada Swalayan Indomaret di Jalan Rajawali Kota Palangka Raya - Rakhmadi Ilham; Dehen Erang; Windy Utami Putri; Rinto Alexandro (FKIP, Universitas Palangka Raya, 2023)
The existence of the modern market has received great attention and welcome from the public, especially the middle to upper economic community due to several things, for example the location is in a strategic place, air conditioned, comfortable, and the promotion of goods offered is cheaper than the price of goods in the market. traditional market. The formulation of the problem in this study is 1) How is the Management of Management Information Systems at Indomaret Supermarkets on Jalan Rajawali Palangkaraya City? 2) What is the role of the management information system at the Indomaret supermarket on Jalan Rajawali, Palangka Raya? 3) What is the role of management information system technology at Indomaret Supermarkets on Jalan Rajawali, Palangka Raya City?. The purpose of this study to identify and describe, namely: 1) Management of the management information system at Indomaret Supermarkets on Jalan Rajawali, Palangka Raya City. 2) The role of management information systems at Indomaret Supermarkets on Jalan Rajawali, Palangka Raya City. 3) The role of management information system technology at Indomaret Supermarkets on Jalan Rajawali, Palangka Raya City. This research was conducted using a qualitative method, an approach that is carried out on all research objects so that the data search process can run easily and according to plan. The location of this research was carried out at Indomaret supermarket on Jalan Rajawali, Palangka Raya city. Sources of research data are primary data sources that are directly given to researchers and source data that are not directly given to researchers, for example through other people or through documents. The data collection procedure is by (1) Observation, (2) Interview, (3) Documentation. Analysis of the data used in this study is a qualitative analysis, namely an analysis that describes what actually happened to the object of research. The results of the study indicate that the management of management information systems must consider the efficiency of the company's data source system in guaranteeing information through the application of management information systems. Research suggestions improve management and management information systems to be more effective and efficient and improve product information.